Clumped-isotope palaeothermometry and LA-ICP-MS U–Pb dating of lava-pile hydrothermal calcite veins - MacDonald, J. M.; Faithfull, J. W.; Roberts, N. M. W.; Davies, A. J.; Holdsworth, C. M.; Newton, M.; Williamson, S.; Boyce, A.; John, C. M. (Contributions to mineralogy and petrology, 2019)
Calcite veins are a common product of hydrothermal fluid circulation. Clumped-isotope palaeothermometry is a promising technique for fingerprinting the temperature of hydrothermal fluids, but clumped-isotope systematics can be reset at temperatures of > ca. 100 °C. To model whether the reconstructed temperatures represent calcite precipitation or closed-system resetting, the precipitation age must be known. LA-ICP-MS U–Pb dating of calcite is a recently developed approach to direct dating of calcite and can provide precipitation ages for modelling clumped-isotope systematics in calcite veins. In this study, clumped-isotope and LA-ICP-MS U–Pb calcite analyses were combined in basalt-hosted calcite veins from three settings in Scotland. Samples from all three localities yielded precipitation temperatures of ca. 75–115 °C from clumped-isotope analysis, but veins from only two of the sites were dateable, yielding precipitation ages of 224 ± 8 Ma and 291 ± 33 Ma (2 σ ). Modelling from the dated samples enabled confident interpretation that no closed-system resetting had occurred in these samples. However, the lack of a precipitation age from the third location meant that a range of possible thermal histories had to be modelled meaning that confidence that resetting had not occurred was lower. This highlights the importance of coupling clumped-isotope thermometry and LA-ICP-MS U–Pb calcite dating in determining the temperature of hydrothermal fluids recorded in calcite veins. This paired approach is shown to be robust in constraining the timing and precipitation temperature of calcite formation, and thus for tracking hydrothermal processes.